Government-based financing strategies for public health in Ukraine: way of transforming. (13th November 2019) - Kovalenko, N; Duda, M; Liashko, V
Abstract: : Since 2016 Ukraine is going through health financing reform. National public health (PH) system functioned with focus only on control of epidemics and sanitary situations. Following EU recommendations, the Government established Center for Public Health (CPH) and adopted the Concept of PH System Development. As new Budget Code comes into force in 2020, PH system must be transformed on institutional and financing level. We conducted policy analyses and developed PH financing options and found that existing budget programs (epidemiological surveillance and purchases of medicines) make up over 70% of the total government PH spending. Public spending was ineffective based on line budget approach without attention to quality and not linked to epidemiological situation. New PH mechanisms will be piloted in 2019 in several regions to calibrate approach and ensure evidence-based policy. Transformed financing model focuses on purchasing PH services rather than maintenance. We selected a phased approach to launch new PH financing mechanism. Procurement system ProZorro allows to follow transparency and good governance principles while purchasing PH services. Using experience with GF's procurements, the CPH will purchase services: HIV and hepatitis prevention among key population, supporting PLWHIV, epidemiological surveillance. Legal framework developed and agreed with stakeholders. This approach allows to shift focus from dealing with consequences to prevention and early revealing of potential PH risks. Provider's staff and network will be optimized. Budget economy is up to 15% in 2019, and additional 5% in 2020. The rebuilding PH system showed that 2019 is an opportunity to develop and pilot new financing approaches. Key step is to ensure that national policy equipped with legislation and recommendations to implement new PH approaches. Pilot results will become a strong base for further PH system development as well as evidence-based policy for effective response to PH needs. Key messages: Public health system in Ukraine is going through reforming process to address existing challenges and introducing new financing approaches with a focus on regional level. Using transparent procurement system to transform the public health financing mechanisms due to existing limitations and overall health financing reform in Ukraine.